VD_FINDINFO HC / 2014 / 14 vom 6. Januar 2014 - VD Tribunal cantonal (2014)
EXPULSION DE LOCATAIRE, DEMEURE DU DÉBITEUR, LOGEMENT DE LA FAMILLE | 169 CC, 257d CO, 266m CO, 266n CO, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH)